Network-bridge structure of CdSxSe1-x nanowire-based optical sensors - Choi, Young-Jin; Park, Kyung-Soo; Park, Jae-Gwan (IOP PUBLISHING LTD, 2010)
We report on the synthesis of CdSxSe1-x nanowires by pulsed-laser deposition and their application to optical sensors. We developed a suspended structure for a nanowire-based optical sensor. This structure comprised separated nanowires that were suspended in the desired position between two pre-patterned electrodes. We found from measuring photoluminescence that the direct bandgap energy of the nanowires changes linearly with the composition of sulfur in the nanowires. These findings show that the bandgap energy of the nanowires can be systematically modulated in the range of 1.7-2.4 eV. The cutoff wavelength of the fabricated optical sensors shifted toward the longer wavelength with increasing sulfur composition. We found that the CdSxSe1-x nanowires have sufficient potential for a broad band optoelectronic device involving photosensors.
Keywords: PULSED-LASER ABLATION; SEMICONDUCTOR NANOWIRES; BUILDING-BLOCKS; PHOTOLUMINESCENCE; NANOSTRUCTURES; MODULATION; NANOBELTS; DEVICES